The Impact of Imperial Rome on Religions, Ritual and Religious Life in the Roman Empire Proceedings from the Fifth Workshop of the International Network Impact of Empire (Roman Empire, 200 B.C. - A.D. 476) Münster, June 30 - July 4, 2004 - de Blois, Lukas; Funke, Peter; Hahn, Johannes (Impact of Empire, 2006)
The fifth volume Impact of Empire (Roman Empire, 200 BC-AD 476) focuses on the impact of imperial Rome on religion, treating connections between Roman expansion and religion; the imperial impact on local cults; priests, priestesses and bishops and the divinity of Roman Emperors. Readership: All those interested in Roman history (also at the local level in communities in the Roman Empire), the history of ancient Greek and Roman religions, the representation of power of Roman emperors, and the connections between centre and periphery within the Roman Empire.